Online Harassment of Female Journalist in Lagos State - Precious Awosanya Oreoluwa; Perpetua Ogechi Vitalis; Alikor Queen Nneka; Joy Collins-Dike; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
This study examines online harassment of female journalist in Lagos State. The objectives of the study is to examine the various types of online harassment faced by female journalist, to explore the coping strategies and support system used by female journalist against online harassment and the strategies and policies put in place to curb online harassment. The study used the Feminist theory to interrogate social problems, trends that have been overlooked such as gender discrimination and structural inequalities. The study employed survey method and online questionnaire was used as an instrument of data collection. The population of the study consists of 250 female journalists. the study discovered that the digital space was popular among female journalist to carry out their job functions, the study further revealed that online harassment is popular in the digital space as most women are harassed while trying to carry out their job functions, that female journalist face challenges such as sexual advances, gender insensitive policies, cultural and religious limitations. The study concludes that women journalists suffer a variety of digital and physical challenges to their freedom of speech. Murder and assault continue to haunt journalists throughout the world, as has internet harassment in the form of rape and death threats, as well as various forms of intimidation, heightened surveillance, impersonation, and other digital dangers. The internet environment has been weaponised, with sophisticated attacks using speed and dispersed networks to promote misogyny, sexism, racism, homophobia, religion and other hate speech.